Identifikasi Nilai Bisnis SI/TI Menggunakan Tabel Manfaat Bisnis SI/TI Generik Ranti: Studi Kasus Disaster Recovery Center Kementerian XYZ - Riskinanto, Anggar (I-STATEMENT, 2017)
The role of IS/IT within an enterprise can be considered as a strategic component. It is so strategic, so companies often expend significant investments to gain the business benefits of IS/IT. Large investments have not necessarily produce the same benefits. It happened at the Ministry of XYZ, where they built a DRC (Disaster Recovery Center) to help the system SISKOHAT (Haji Integrated Information System). Required an analysis of the business benefits that can be obtained from the development of this system. Based on the analysis, obtained two categories of the business benefits of IS / IT, ie: Decrease / Suppress Costs (RCO) and Reducing Risk (RRI). The second category of these business benefits, obtained three sub-categories of the business benefits of IS / IT, ie: Failure Cost Service (RCO-05), Doubtful (RRI-02), and Data Loss (RRI-05).